2005
DOI: 10.1007/s00428-005-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of JC virus DNA sequences in colorectal cancers in Japan

Abstract: JC virus (JCV), a ubiquitous polyoma virus that commonly infects humans, was first identified as the etiologic agent for the fetal demyelinating disease, progressive multifocal leukoencephalopathy. Recently, a number of reports have documented detection of JCV in samples derived from several types of neural as well as non-neural human tumors. It has been suggested that oncogenicity of JCV depends on a T antigen having a strict structural homology to the T antigen of simian virus 40. To clarify whether JCV migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 29 publications
(44 reference statements)
3
81
2
5
Order By: Relevance
“…In our previous study, it was found that JCV T antigen existence or copies were closely linked to the lung, tongue, pharyngeal and gastric carcinogenesis (10,14,15,20). Hori et al (9) reported that T antigen was detected in 6 of 23 colorectal cancer cases (26.1%) and 1 of 21 adenomas (4.8%), but none of the 20 samples of normal colonic mucosa. These findings indicated that JCV T antigen may be involved in the malignant transformation of epithelium as evidenced by our transgenic lens tumor induced by T antigen, although we failed to establish the animal model of gastric tumor induced by the JCV T antigen (28).…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, it was found that JCV T antigen existence or copies were closely linked to the lung, tongue, pharyngeal and gastric carcinogenesis (10,14,15,20). Hori et al (9) reported that T antigen was detected in 6 of 23 colorectal cancer cases (26.1%) and 1 of 21 adenomas (4.8%), but none of the 20 samples of normal colonic mucosa. These findings indicated that JCV T antigen may be involved in the malignant transformation of epithelium as evidenced by our transgenic lens tumor induced by T antigen, although we failed to establish the animal model of gastric tumor induced by the JCV T antigen (28).…”
Section: Discussionmentioning
confidence: 95%
“…Ten studies, with sample sizes ranging from 18 to 186, detected JCV genomic sequences in 9-89% of colorectal carcinomas and 5-82% of adenomatous tissue (Laghi et al, 1999;Theodoropoulos et al, 2005; R. Hori et al, 2005;Casini et al, 2005;Enam et al, 2002;Goel et al, 2006;P. Y. Lin et al, 2008, Niv et al, 2010aKarpinski et al, 2011;Jung et al, 2008).…”
Section: Cancer In Humanmentioning
confidence: 99%
“…The contribution of Tag of JC polyomavirus to human colon carcinogenesis was investigated in several studies with controversial results (Newcomb et al, 2004;Hori et al, 2005;Weinreb, 2006). Vil-Cre  LoxP-Tag mice allowed the analysis of Taginduced tumorigenesis in the colon, which, however, was hampered by tumors in the thymus and Tag-specific CTL tolerance.…”
Section: Sporadic Colorectal Cancer Modelmentioning
confidence: 99%